Peluang dan Tantangan Pengembangan Usaha Mikro Kecil Menengah (UMKM) dari Berbagai Aspek Ekonomi - I Putu Septian Adi Prayuda; Abdul Basit; Yudhi Kurniawan Zahari; Reza Arviciena Sakti (Masyarakat Ekonomi Syariah Bogor, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are productive economic entities owned by individuals or private business entities that meet the criteria for micro, small, or medium enterprises. In practice, MSME actors face various challenges and issues frequently encountered in the development of MSMEs. This study aims to identify the opportunities and challenges in the development of Micro, Small, and Medium Enterprises (MSMEs) from various economic aspects. The study is interested in examining the conditions of MSMEs that manage to survive under pressure, delving deeper into and providing an analysis of the challenges faced by MSMEs as well as the opportunities that can be leveraged to improve their performance, using a systematic literature review method. It is hoped that this study will provide further policy recommendations to enhance MSME strength as an opportunity and empower MSMEs in facing various challenges. The research findings indicate that Digital Marketing, Human Resources (HR), and Financial Literacy play crucial roles in creating markets and integrating into global supply chains. However, to ensure that the digital economy benefits MSME growth in Indonesia optimally, challenges such as limited access and technology infrastructure, as well as deficiencies in financial literacy, digital marketing, and human resources, need to be effectively addressed. MSMEs that can adapt to technological advancements and innovate their products will be able to compete with their rivals in the increasingly advanced digital economy.